Comparison of Clinical Outcomes Following Lumbar Endoscopic Unilateral Laminotomy Bilateral Decompression and Minimally Invasive Transforaminal Lumbar Interbody Fusion for One-Level Lumbar Spinal Stenosis With Degenerative Spondylolisthesis - Hua, Wenbin; Wang, Bingjin; Ke, Wencan; Xiang, Qian; Wu, Xinghuo; Zhang, Yukun; Li, Shuai; Yang, Shuhua; Wu, Qiang; Yang, Cao (Frontiers in Surgery, 2021)
Introduction: Both lumbar endoscopic unilateral laminotomy bilateral decompression (LE-ULBD) and minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) have been used to treat one-level lumbar spinal stenosis (LSS) with degenerative spondylolisthesis, while the differences of the clinical outcomes are still uncertain. Methods: Among 60 consecutive patients included, 24 surgeries were performed by LE-ULBD and 36 surgeries were performed by MI-TLIF. Patient demographics, operation characteristics and complications were recorded. Sagittal parameters, including slip percentage (SP) and slip angle (SA) were compared. The visual analog scale (VAS) score, the Oswestry Disability Index (ODI) score, and Macnab criteria were used to evaluate the clinical outcomes. Follow-up examinations were conducted at 3, 6, 12 and 24 months postoperatively. Results: The estimated blood loss, time to ambulation and length of hospitalization of LE-ULBD group were shorter than MI-TLIF group. Preoperative and final follow-up SP of the LE-ULBD group was of no significant difference, while final follow-up SP of the MI-TLIF group was significantly improved compared with preoperative SP. The postoperative mean VAS and ODI scores decreased significantly in both groups. According to the modified Macnab criteria, the outcomes rated as excellent/good rate were 95.8% and 97.2% in the two groups. One case of intraoperative epineurium injury was observed in the LE-ULBD group. No nerve injury, dural injury or cauda equina syndrome was observed in MI-TLIF group. Conclusion: Both LE-ULBD and MI-TLIF are safe and effective to treat one-level LSS with degenerative spondylolisthesis.